Inbound Marketing Based On Content And Customer In The Creative Industry Selling Fresh Meat, Seafood And Vegetables In Yogyakarta: An Experimental Approach - Dewa, Chriswardana Bayu; Pradiatiningtyas, Diah; Safitri, Lina Ayu (Universitas Bina Sarana Informatika, 2024)
Covid-19 had an impact on decreasing GDP in the livestock sector, namely by 1.8%. The strategy to improve this sector is to carry out inbound marketing through the use of websites, blogs and social media. This research applies an inbound marketing method based on content and customers to develop product marketing in the creative industry selling meat, seafood and fresh vegetables in Yogyakarta. The research method used is an experimental research method. There are two groups of respondents in this research, namely respondents from generation The respondents selected were 200 housewives from generation X and generation Y. Data was obtained using a questionnaire. The data analysis used was MANOVA with SPSS 25. The results of the study showed that there was no difference between advertising for the sale of meat, vegetables and seafood or without advertising on purchasing interest in generation X and generation Y.